2021
DOI: 10.3390/cancers13071689
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Response Patterns in Renal Cell Carcinoma Treated with Immune Checkpoint Inhibitors—Navigating the Radiologic Potpourri

Abstract: Background: Atypical response patterns have been a topic of increasing relevance since the advent of immune checkpoint inhibitors (ICIs), challenging the traditional RECIST (Response Evaluation Criteria in Solid Tumors) method of tumor response assessment. Newer immune-related response criteria can allow for the evolution of radiologic pseudoprogression, but still fail to capture the full range of atypical response patterns encountered in clinical reporting. Methods: We did a detailed lesion-by-lesion analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…DR2 and DR3 were observed in 44% and 10% of patients, respectively, and the rate of DR1 was 8%, which was consistent with previous evaluation criteria for DR. Similarly, Wong et al 13 reported a relatively high frequency of DR (47.8%), where DR was defined as a mixed response with new lesions, as well as mixed stable and progressing or regressing lesions. Thus, the rate of DR occurrence could be overestimated because of the incorporation of stable target lesions for DR evaluation.…”
Section: Definition Of Immune-related Dr By Radiological Evaluation C...mentioning
confidence: 89%
See 3 more Smart Citations
“…DR2 and DR3 were observed in 44% and 10% of patients, respectively, and the rate of DR1 was 8%, which was consistent with previous evaluation criteria for DR. Similarly, Wong et al 13 reported a relatively high frequency of DR (47.8%), where DR was defined as a mixed response with new lesions, as well as mixed stable and progressing or regressing lesions. Thus, the rate of DR occurrence could be overestimated because of the incorporation of stable target lesions for DR evaluation.…”
Section: Definition Of Immune-related Dr By Radiological Evaluation C...mentioning
confidence: 89%
“… 11 In an open, nonrandomized, current care study, 62 NSCLC patients were scheduled to initiate immunotherapy as their first or later systemic treatment and were prospectively evaluated, and five patients developed DR. 12 Different ICI monotherapies, including nivolumab, pembrolizumab, and atezolizumab, contribute to the occurrence of DR. DR has also been found in patients receiving combination immunotherapy, such as nivolumab in combination with ipilimumab and PD-1/PD-L1 inhibitors in combination with chemotherapy, targeted therapy, or radiotherapy. 13 , 14 In a retrospective study including 360 cancer patients who participated in clinical trials for combination immunotherapy, DR was observed in 12 (3.3%) patients and PsPD in 10 (2.8%) patients. 14 Several metastatic solid tumors, including NSCLC and RCC, can develop as DR after immunotherapy.…”
Section: Frequency Of Immune-related Drmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the abscopal response patterns were very divergent between the patients. Most patients experienced isolated abscopal responses in one to two lesions, while two patients presented a more extensive response in lung and liver [100].…”
Section: Kidney Cancermentioning
confidence: 98%